Systematic review: preoperative psychological factors and total hip arthroplasty outcomes - John P. O’Connor; Paige Holden; Joel J. Gagnier (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Total hip arthroplasties (THA) are cost-effective interventions for patients with osteoarthritis refractory to physical therapy or medical management. Most individuals report positive surgical outcomes with reduction in pain and improved joint function. Multiple recent studies demonstrated the influence of patient mental health on surgical success. We sought to determine the relationship between patient preoperative psychological factors and postoperative THA outcomes, specifically pain and function. Methods PubMed, EMBASE and Cochrane Reviews databases were queried using terms “(mental OR psychological OR psychiatric) AND (function OR trait OR state OR predictor OR health) AND (outcome OR success OR recovery OR response) AND total joint arthroplasty).” A total of 21 of 1,286 studies fulfilled inclusion criteria and were included in the review. All studies were analyzed using GRADE and Risk of Bias criteria. Results Overall, compared to cohorts with a normal psychological status, patients with higher objective measures of preoperative depression and anxiety reported increased postoperative pain, decreased functionality and greater complications following THA. Additionally, participants with lower self-efficacy or somatization were found to have worse functional outcomes. Conclusions Preoperative depression, anxiety and somatization may negatively impact patient reported postoperative pain, functionality and complications following THA. Surgeons should consider preoperative psychological status when counseling patients regarding expected surgical outcomes. Level of evidence 3.